The Role of Adherence to Social, Economic and Political Values in Cultural and Moral Development - Farzaneh Alaei; Faizullah Norouzi; Hossein Dehqan (International Journal of Ethics and Society)
Introduction: Cultural development means creating transformation and creating values, moral relationships and appropriate norms that provide the necessary grounds in the form of society to satisfy human needs. Understanding concepts such as development, culture and cultural development is important to the fate of nations and Iranian society. The purpose of this research is to investigate the role of social, economic and political values on cultural and moral development from the perspective of Tehran citizens. Material and methods: The present research was applied, and its theoretical framework was based on the theory of Parsons and Inglehart. The research method used was a quantitative survey. The statistical population of this research included all citizens over 15 years of age living in Tehran. For sample selection, taking into account Cochran's formula and a 10% error rate, the sample size was equal to 422 people, which reached 388 people after removing outliers. The sampling method was a multi-stage cluster. The research tool was a researcher-made questionnaire. The data were analyzed using the Pearson correlation method. Results: The research results indicate that there is a significant relationship between cultural-ethical development and social value (r = 0.478), economic value (r = -0.295), and political value (r = 0.297). Conclusion: Adherence and respect for social and political values (commitment, honesty and adherence to family relations; political awareness; political activity and presence; institutional trust; materialism and utilitarianism) lead to the improvement of cultural and moral development. But paying attention only to economic values (materialism and utilitarianism) has an inverse and negative relationship with cultural and moral development.